(3GdeZfj aj JOHjQ GdCeQGV heYQaI GdYdd hGdCYQGVs - (3CHh GdMSf SYjO Hf gHg Gddg Hf GdMSjf GdajdSha,J (B495 (3g` s ((3CMeO Hf bQI s)
(3ChdgG (B:s
(3HYO GdHSedI (B: (3bGd GdTjN GdEeGe Ef Chd eG fWb Hg GddSGf hKHJ QgGfg ai GdLfGf GdMeO deOHQ GdCReGf GdPi ChLO GdeNdhbGJ hHYO aGdQZHI EdG Gddg JYGdi ai EOeGfg ef NUg ef NdbI s
(3BNQgG (B:s
(3hYGdL GdeQjV HYdGL GdeHQSe , hGddg GdTGai GdeYGai , hdg GdMeO hGdTcQceG gh Cgdg s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B156s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B237 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs